Submicroscopic and Asymptomatic Congenital Infection by Plasmodium vivax or P. falciparum in Colombia : 37 Cases with Placental Histopathology and Cytokine Profile in Maternal and Placental BloodSubmicroscopic and Asymptomatic Congenital Infection by Plasmodium vivax or P. falciparum in Colombia: 37 Cases with Placental Histopathology and Cytokine Profile in Maternal and Placental Blood (2017)
ABSTRACT: Problem. Congenital plasmodial infection (CPI) is a rare event, which has been little studied in Colombia. Objective. To measure the frequency of CPI and to describe the immune and histological characteristics in maternal blood and placentas when CPI occurs. Methodology. A cross-sectional study was carried out in northwest Colombia. A sample size of 39 unit analysis (a unit of analysis corresponds to the cord, placenta, and peripheral blood of a pregnant woman) was calculated using epidemiological and statistical parameters. Thick blood smear (TBS) and quantitative real-time polymerase chain reaction (qPCR) were used as diagnostic tests. Results and Conclusions. A total of 137 parturient women were studied. All cases of CPI were submicroscopic (TBS negative and qPCR positive) and asymptomatic infections. If the definition of CPI considers only detection of parasites in umbilical cord blood, regardless of what was found in peripheral or placental blood, the frequency of CPI was 27%. However, if that definition is stricter and includes simultaneous detection of parasites in maternal or placental blood with the same species, the frequency of CPI in this study was 13%.